Pigment bioproduction by Monascus purpureus using corn bran, a byproduct of the corn industry - Almeida, Adrielle Borges de; Santos, Nathalia Horrana; Lima, Thayanara Mayara de; Santana, Railany Vieira; Oliveira Filho, Josemar Gonçalves de [UNESP]; Peres, Daiane Sousa; Egea, Mariana Buranelo (Elsevier, 2021)
Monascus purpureus is an ascomycete known for decades for producing several metabolites of commercial interest. The objective of this work was to optimize the production of pigments of M. purpureus using submerged fermentation with corn bran. An experimental design containing 11 tests was realized twice to determine the best concentration of corn bran and peptone in submerged fermentation to produce higher red pigment concentration (AU500). After the best substrate concentration was chosen, pigment production was evaluated up to 20 days of submerged fermentation. Antioxidant and antibacterial activities and thermal and pH stabilities of the pigment extract were also evaluated. The optimized concentration (42.5 g/L of corn bran and 30 g/L of peptone) was used in submerged fermentation for 6 days to produce the pigment extract. The pigment extract showed high antioxidant activity, twice as much as the substrate (corn bran) used in its production. The pigment extract produced by M. purpureus presented thermal (sterilization and 40–80 °C in hot dry) and pH (4–7) stabilities. Thus, the production of pigment from M. purpureus can be an alternative use for corn bran utilization.
Keywords: Bioprocess; Byproduct; Natural red pigment; Waste valorization